PERANCANGAN APLIKASI PEMETAAN CUSTOMER BERBASIS WEBGIS DENGAN MENGGUNAKAN METODE K-MEANS - DickyZulkarnain; Fauzi, Rahmat (Computer Science and Industrial Engineering, 2022)
J&T Express is a supplier of products conveyance administrations inside the city and outside the city, J&T Express has outlet branches in several areas in Batam, Of the many expedition services we know in Indonesia, J&T Express is a newcomer who immediately succeeds in capturing the hearts of customers. There are also many online businesses that have partnered with J&T Express. To obtain and add customers, a special strategy is needed so that the marketing carried out is more effective and efficient, so in this study it was carried out by processing existing customer data. WebGIS is an electronic geographic data framework, which is an application that can be run and applied to an internet browser whether the application is in a worldwide PC organization, in particular the web or in a Network in view of a Local Area Network (LAN) or in a Personal Computer (PC) but has ndi s configured in the network settings on the web server. The method used is K-Means which is one of the clustering algorithms aimed at dividing data into groups. In this study information assortment was acquired through perception, interviews and documentation.The consequence of this study is that this framework can be utilized to help the admin department of J&T express. In this system, there is a data analysis function which will issue the results of the analysis data on the delivery of customer packages that have been clustered along with information on giving cashback to customers to increase trust in customers